Geisha in rivalry - Nagai, Kafu 1879-1959 (Library of Japanese literature, 1963)
Against the backdrop of Tokyo's Shimbashi district, vivid characters Rikiji, Kikuchiyo, and the heroine Komayo play out their drama of illicit love, shady intrigue, and unrelenting rivalry.